2023
DOI: 10.1111/1365-2656.13910
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of host–parasite coinvasion promote enemy release and specialist parasite spillover

Abstract: Species invasion and redistribution, driven by climate change and other anthropogenic influences, alter global biodiversity patterns and disrupt ecosystems. As host species move, they can bring their associated parasites with them, potentially infecting resident species, or leave their parasites behind, enhancing their competitive ability in their new ranges. General rules to predict why invading hosts will retain some parasites but not others are relatively unexplored, and the potential predictors are numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Indeed, metabarcoding and qPCR analysis suggest that those two OTUs dominate the microbiota of intermediate and native populations but not that of recently introduced ones. A recent study on parasite infection in invasive species has shown that parasite characteristics are reliable to predict parasite retention ( 76 ). The authors even demonstrated that specialist parasites (like A. taiwanensis ) are usually more persistent to coinvade with their native host.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, metabarcoding and qPCR analysis suggest that those two OTUs dominate the microbiota of intermediate and native populations but not that of recently introduced ones. A recent study on parasite infection in invasive species has shown that parasite characteristics are reliable to predict parasite retention ( 76 ). The authors even demonstrated that specialist parasites (like A. taiwanensis ) are usually more persistent to coinvade with their native host.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, metabarcoding and qPCR analysis suggest that those two OTUs dominate the microbiota of intermediate and native populations but not that of recently introduced ones. A recent study on parasite infection in invasive species has shown that parasite characteristics is reliable to predict parasite retention (76). The authors even demonstrated that specialist parasites (like As.…”
Section: Discussionmentioning
confidence: 99%